Effects Of Polarity Parameter On Machining Of Tool Steel Workpiece Using Electrical Discharge Machining - Mohamed Reza Zalani, Mohamed Suffian; Mas Ayu, Hassan; Siti Haryani, Tomadi; Rosdi, Daud (2010)

(untitled)
Electrical discharge machining (EDM) has been recognized as an efficient production method for precision machining of electrically conducting hardened materials. This research studies the effect of polarity on the material removal rate (MRR), electrode wear ratio (EWR) and surface roughness (SR) of the tool steel work piece machining using EDM. Design of experiments (DOE) using L18 orthogonal arrays were being selected and the results being represents using response graph. Wrong polarity can have significant implications on speed, wear, and stability and to investigate this phenomenon using L18 orthogonal arrays design of experiment. The optimum parameters and the effects of polarity to the material removal rate (MRR), electrode wear ratio (EWR) and surface roughness (SR) are being discussed.